Numerical Modeling of Stagnation Flows over Porous Catalytic Surfaces - Karadeniz, Hüseyin (KIT Scientific Publishing, 2016)
In this book, stagnation flows on a catalytic porous plate is modeled one-dimensionally coupled with multi-step surface reaction mechanisms and molecular transport (diffusion and conduction) in the flow field and in the porous catalyst. Internal and external mass transfer limitations as well as possible reaction routes in the catalyst are investigated for CO oxidation, WGS reaction, partial and steam reforming of methane over Rh/Al?O?.
English
Keywords: Heterogeneous catalysis; Stofftransportlimitierungen; Reaktion-DiffusionStagnation-flow reactor; Staupunktreaktor; Reaction-Diffusion; Heterogenen Katalyse; External and internal mass transfer limitation